2020
DOI: 10.1149/2162-8777/ab8b4c
|View full text |Cite
|
Sign up to set email alerts
|

HVPE Growth and Characterization of ε-Ga2O3 Films on Various Substrates

Abstract: In this study we compare the growth of gallium oxide films by halide vapor phase epitaxy (HVPE) on various substrates under the same growth conditions. Gallium oxide films were deposited at 500 °C–600 °C on basal plane (0001) planar and patterned sapphire substrates, (0001) 2H-GaN, 4H-SiC, and 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(37 citation statements)
references
References 34 publications
(63 reference statements)
1
29
0
2
Order By: Relevance
“…50 A lower mismatch between the substrate and the e-Ga 2 O 3 epilayer also appears to facilitate the growth of this phase; with the same HVPE growth conditions that resulted in a-Ga 2 O 3 layers on c-plane sapphire substrates, (001)-oriented e-Ga 2 O 3 was obtained on GaN(0001), AlN(0001), and b-Ga 2 O 3 (% 201), the latter exhibiting superior crystal quality. 29,[88][89][90] A similar trend has been reported for Mist-CVD growth, where the use of MgO(111) instead of YSZ(111) substrates (with 2.5 and 20% nominal mismatch with e-Ga 2 O 3 , respectively) allowed one to obtain single-phase (001)-oriented e layers at much lower temperatures. 86 However, a quantitative comparison of literature results based on the reported mismatch could be misleading, as the nominal lattice constant of the substrate might not be the View Article Online parameter determining the effective mismatch.…”
Section: Substrate and Lattice Matchmentioning
confidence: 58%
See 1 more Smart Citation
“…50 A lower mismatch between the substrate and the e-Ga 2 O 3 epilayer also appears to facilitate the growth of this phase; with the same HVPE growth conditions that resulted in a-Ga 2 O 3 layers on c-plane sapphire substrates, (001)-oriented e-Ga 2 O 3 was obtained on GaN(0001), AlN(0001), and b-Ga 2 O 3 (% 201), the latter exhibiting superior crystal quality. 29,[88][89][90] A similar trend has been reported for Mist-CVD growth, where the use of MgO(111) instead of YSZ(111) substrates (with 2.5 and 20% nominal mismatch with e-Ga 2 O 3 , respectively) allowed one to obtain single-phase (001)-oriented e layers at much lower temperatures. 86 However, a quantitative comparison of literature results based on the reported mismatch could be misleading, as the nominal lattice constant of the substrate might not be the View Article Online parameter determining the effective mismatch.…”
Section: Substrate and Lattice Matchmentioning
confidence: 58%
“…82 An interesting contribution about the role of the substrate in the nucleation of the a or e phase is given in ref. 90 and 96, using HVPE to grow Ga 2 O 3 on column-patterned sapphire. While the standard deposition on bare c-plane sapphire results in a-Ga 2 O 3 with good crystallinity, the film on patterned substrates gives a mixture of a and e-Ga 2 O 3 , with a-Ga 2 O 3 vertical columns originating from the cones on the sapphire substrate, protruding up to the surface and capped with an irregular shape faceted pyramid on top.…”
Section: Substrate and Lattice Matchmentioning
confidence: 99%
“…Ga 2 O 3 epitaxial films grown on gallium nitride (GaN), SiC, and other hexagonal or pseudohexagonal substrates exhibit hexagonal symmetry. [3,4] Previously this type of crystal structure was considered to be a distinct ε polymorph with hexagonal (P6 3 mc space group) lattice. However, recent findings [2] showed that ε-Ga 2 O 3 is not single crystalline and is formed by nanoscale rotational domains of the κ-Ga 2 O 3 polymorph with orthorhombic (Pna2 1 space group) structure.…”
Section: Introductionmentioning
confidence: 99%
“…Достигнут значительный прогресс в выращивании эпитаксиальных пленок [1][2][3][4][5][6][7][8][9]. Корундообразная α-фаза обладает среди всех политипов оксида галлия наибольшей шириной запрещенной зоны E g , не менее 5.3 эВ, и при легировании Sn или Si имеет высокую донорную проводимость [3,8,[10][11][12][13][14][15]. В то же время ε-фаза с E g , близкой к 4.9 эВ [1,2,16], является второй после β-Ga 2 O 3 по температурной стабильности.…”
Section: Introductionunclassified